Ovulation induction by metformin among obese versus non-obese women with polycystic ovary syndrome - Yazed Sulaiman Al-Ruthia; Hazem Al-Mandeel; Hisham AlSanawi; Wael Mansy; Reem AlGasem; Lama AlMutairi (Elsevier, 2017)
Objectives: There is some evidence that the efficacy of metformin as an ovulation stimulation agent depends on the body mass index (BMI) of the treated anovulatory women with polycystic ovary syndrome (PCOS). The aim of this study was to examine the likelihood of successful ovulation among obese (BMI ⩾30 kg/m2) versus non-obese (BMI <30 kg/m2) women with PCOS. Methods: A total of 243 medical charts of women with PCOS who visited King Khaled University Hospital (KKUH) in Riyadh, Saudi Arabia, between 2006 and 2012 were reviewed. Patients' sociodemographic, laboratory, and medical data were collected. Descriptive statistics and multiple logistic regression analyses were performed to compare the patients' baseline data and successful ovulation among the obese and non-obese anovulatory women with PCOS, respectively. Results: One hundred and nine women with PCOS who were prescribed metformin for ⩾3 months were included in the study. Almost 60% of the women who were included in the study were obese. The likelihood of ovulation among obese women with PCOS was 77.9% (odds ratio = 0.221, 95% CI 0.052-0.947, P = 0.042) less than that in their non-obese counterparts. Conclusion: The findings of this study suggest that metformin is more effective as an ovulation stimulation agent when administered to non-obese women with PCOS. Lifestyle modifications such as diet and exercise should be emphasized upon as an integral part of any treatment plan for PCOS.